Successful treatment with tacrolimus in TAFRO syndrome: two case reports and literature review. Issue 23 (June 2018) - Shirai, Taiichiro; Onishi, Akira; Waki, Daisuke; Saegusa, Jun; Morinobu, Akio
Abstract: Rationale: TAFRO syndrome is a systemic inflammatory disorder characterized by thrombocytopenia, anasarca, fever, reticulin fibrosis, renal dysfunction, and organomegaly. In contrast to that in multicentric Castleman disease, interleukin-6 targeting strategies seem ineffective in some TAFRO syndrome cases; however, the optimal treatment remains unclear. Here, we report 2 cases of TAFRO syndrome, where 1 with cardiomyopathy, successfully treated with tacrolimus. This is the first case report of successful treatment with tacrolimus in TAFRO syndrome. Patient concerns: Both patients (cases 1 and 2) developed fever, anasarca, thrombocytopenia, renal dysfunction, and mild hepatosplenomegaly. Diagnoses: In both patients, lymph node pathology revealed mixed type Castleman disease-like features, and bone marrow showed reticulin myelofibrosis. TAFRO syndrome was diagnosed based on the patients' laboratory, clinical, and pathologic findings. In case 2, we observed a rare complication of cardiomyopathy with no evidence of takotsubo cardiomyopathy or viral myocarditis. Interventions and outcomes: In case 1, tocilizumab combined with glucocorticoids was ineffective and caused septic shock; additionally, cyclosporine A was discontinued because of hepatotoxicity. However, tacrolimus was effective in resolving TAFRO syndrome without any adverse events. In case 2, tacrolimus completely reversed TAFRO syndrome and was also effective in cardiomyopathy. Lessons: This report suggests that tacrolimus is potentially effective and safe as an initial treatment and a glucocorticoid-sparing agent. Our literature review shows that calcineurin inhibitors, including tacrolimus, may be effective in TAFRO syndrome. Since previous studies indicate a role of Th1 inflammation in TAFRO syndrome pathogenesis, tacrolimus may, therefore, be effective in treating TAFRO syndrome.